Business and society (McGraw-Hill, 1996)
Since winning a national book award in 1966, this classic, authoritative text has continued to cover both the major research findings of business and societal relations and the thoughts and actions of business practitioners who have struggled both successfully and unsuccessfully with tough human and social problems. The 8th edition covers many important emerging developments that will shape the organizational, social and public policy environments in which students will soon live and work. Many important topic areas have been substantially revised, including ecological and natural resources issues, global challenges, and the complex relationship between science, technology and the media in the age of information. Two new coauthors, Anne Lawrence (San Jose University) and James Weber (Duquesne University), bring valuable experience and perspectives to the author team. Ten cases (five new) bring issues to life.